User Experience (Ux) sebagai Bagian dari Pemikiran Desain dalam Pendidikan Tinggi Desain Komunikasi Visual - Mendiola B. Wiryawan (Bina Nusantara University, 2011)
Digital world, internet and mobile have made communication does not move in one way anymore. Visual Communication as a part of Communication recently is going to be more personal, segmented, interactive, user-generated content, accessible and available in huge quantities. In the positive side, users have more options to receive or to respond communication signals according to his/her needs and wants. In opposite, now everybody gets information clutter caused by unbalanced information between what we can received and what we can digested. For that reason we need method to study the people as an object of our communication. Learning user experience concept make us understand more about our object insight. The aim of this paper is to review principles that used in UX study. In the future we expect this discourse will be assesed and used in a design thinking method and developed in visual communication design institution. Research method used in this paper is based on literatural studies. Understanding of UX will help designers developing design that can be effectively communicate with their segement.